(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: The most difficult aspect of an orthodontic treatment plan is often keeping teeth in their proper placements following treatment. Relapse after orthodontic treatment is typically seen as a return to the initial malocclusion. Relapse, on the other hand, might be defined as any unfavorable shift in tooth position after orthodontic treatment away from a corrected malocclusion. However, a return to the previous malocclusion does not always occur. These modifications might potentially be the outcome of typical aging-related effects. Patients undergoing orthodontic treatment must have a good grasp of the causes of relapse and be knowledgeable about various strategies for preventing it. The aim of this study was to determine the Knowledge and attitude of orthodontic patients towards orthodontic relapse in Saudi Arabia. Methods: This study created use of a structured questionnaire that the authors created for an across-successional study questionnaire survey that would be carried out in Saudi Arabia (SA). The study's population consisted of Saudi patients who had undergone orthodontic intervention. The study’s population comprised Saudi patients classified as adults who aged 19 years or older. The recruitment of participants took place during the months of September 2023 to September 2024, drawing from patients seeking orthodontic treatment across multiple orthodontic clinics situated in various locations within Saudi Arabia. Results: The study involved 304 individuals, a significant 93.8% were aware of the necessity for retention appliances post-treatment, with 45.7% believing they should be used universally. Awareness of potential relapse was reflected in 60.5% acknowledging that perfect treatment outcomes do not ensure stability. Preferences for retention duration varied, with 36.2% suggesting one to three years and 30.3% advocating for lifelong retention. Notably, 64.5% favored bonded retention devices, while 79.3% considered stable results extremely important, and 77.6% opposed charges for recall visits. Satisfaction with teeth alignment was high at 83.2% upon treatment completion but dropped to 60.9% over time. Nearly half reported no significant changes in crowding or bite, yet 42.8% desired further treatment, indicating concerns about retainer adherence. Compliance issues were evident as over half used removable retainers, but a similar percentage had ceased wearing them. Among current retainer users, 37.9% wore them for over 21 hours daily, indicating variable adherence. Overall, 42.8% of participants had a moderate level of knowledge about orthodontic relapse, while 22.0% exhibited a high level and 35.2% were classified as having low knowledge. Conclusion: a significant majority of the study participants 93.8% were aware of the necessity of retention appliances post-treatment, the findings indicate relatively high knowledge levels; however, a concerning number of participants exhibited compliance issues, with nearly half discontinuing the use of retainers. This highlights the need for enhanced patient education and ongoing engagement throughout the retention period to sustain treatment outcomes. Given that satisfaction with teeth alignment declined over time, there is a clear pathway for orthodontists to improve follow-up practices and ensure that patients understand the long-term significance of their retention protocols.